The Ecological Role of Salamanders as Predators and Prey (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Salamanders are relevant components of many terrestrial and aquatic ecosystems. However, despite the importance of salamanders in many resource–consumer networks, their functional role remains remarkably understudied. Therefore, this volume, entitled The Ecological Role of Salamanders as Prey and Predators, provides an opportunity for researchers to highlight the new research on the ecological role of salamanders and newts in prey–predator systems, their trophic behavior, and the variability of their trophic niche in space and time. Various innovative methods, such as COI metabarcoding and network analysis, are applied in the present study to test both the classical and new hypotheses concerning the trophic ecology of salamanders and their interactions with their prey. The present volume is composed of one review and seven research papers, all of which are published after undergoing a complete and impartial peer-review process.